Factors Influencing the Whistleblowing Behaviour: A Perspective from the Theory of Planned Behaviour - Rustiarini, Ni Wayan; Sunarsih, Ni Made (Asian Journal of Business and Accounting, 2017)
Research aim: This study aims to analyse the factors that influence the whistleblowing behaviour of auditors in the public sector by employing the Theory of Planned Behaviour. Design/ Methodology/ Approach: A survey involving 125 government auditors working in the auditor board in Bali, Indonesia is conducted. The data collected are analysed through Structural Equation Modeling (SEM). Research findings: Results indicate that perceived behavioural control plays a significant role on the whistleblowing intention and behaviour of the whistleblowers. However, their attitude towards whistleblowing and their subjective norms are found to have insignificant effects on the whistleblowing intention. This study also finds a positive relationship between whistleblowing intention and whistleblowing behaviour. Theoretical contribution/ Originality: Despite the vast literature on whistleblowing behaviour, this phenomenon has not been wellresearched in the context of Indonesia. In that regard, this study hopes to fill the gap by investigating this issue from the Indonesian government auditors’ perspective. Practitioner/ Policy implication: This research is expected to benefit the regulators and audit firms that are striving to enhance the ethicality of their auditors. In that regard, it also facilitates in protecting the country from abusive and corrupted practices which can cause losses for the country. Research limitation/ Implications: While whistleblowing behaviour may be influenced by numerous factors, this study only considers the individual factors. Hence, future research should incorporate organisational, situational, and demographics factors in investigating the issue. Keywords: Auditor, Behaviour, Corruption, Fraud, Whistleblowing JEL Classification: M40